Work–Family Conflict and Job Satisfaction: Emotional Intelligence as a Moderator. (27th September 2012) - Gao, Yongdong; Shi, Junqi; Niu, Qikun; Wang, Lei
Abstract: The negative impact of work–family conflict (WFC) on employees' well‐being and job‐related outcomes has attracted much research attention recently. A major gap in the literature is which factors could potentially buffer its negative effect on employees. The present study examined the moderating effect of emotional intelligence on the relationship between WFC and job satisfaction in a sample of 212 Chinese high school teachers. On the basis of conservation of resource theory, we hypothesized that emotional intelligence would weaken the negative effect of family‐to‐work and work‐to‐family interference on job satisfaction. Results suggested that WFC (work‐to‐family interference and family‐to‐work interference) was negatively related to job satisfaction and that emotional intelligence weakened the effect of WFC on job satisfaction. These findings provide implications for theories on WFC and emotional intelligence, such as conservation of resource theory. The current study also provides a test of these theories in Chinese culture to support the generalizability of theories developed in previous research. Practical implications for reducing the negative influence of WFC on employees' job satisfaction are also provided, such as the potential value of emotional intelligence for the training and development of employees in teaching professions. Copyright © 2012 John Wiley & Sons, Ltd.